2018
DOI: 10.3389/fphar.2018.01331
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Auger Electron Emitter 111In Delivered by Modular Nanotransporter for Treatment of Bladder Cancer With EGFR Overexpression

Abstract: Gamma-ray emitting 111In, which is extensively used for imaging, is also a source of short-range Auger electrons (AE). While exhibiting negligible effect outside cells, these AE become highly toxic near DNA within the cell nucleus. Therefore, these radionuclides can be used as a therapeutic anticancer agent if delivered precisely into the nuclei of tumor target cells. Modular nanotransporters (MNTs) designed to provide receptor-targeted delivery of short-range therapeutic cargoes into the nuclei of target cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 72 publications
1
36
0
3
Order By: Relevance
“…When 111 In was delivered into the nuclei of target cancer cells via MNT, its cytotoxicity was markedly greater than that of the free 111 In used as a control. These data correspond to those previously reported (Slastnikova et al, 2017b;Rosenkranz et al, 2018). However, 111 In-NOTA-MNT N-affibody and 111 In-NOTA-MNT C-EGF demonstrates higher cytotoxicity than 111 In-NOTA-MNT N-EGF ( Figure 8).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…When 111 In was delivered into the nuclei of target cancer cells via MNT, its cytotoxicity was markedly greater than that of the free 111 In used as a control. These data correspond to those previously reported (Slastnikova et al, 2017b;Rosenkranz et al, 2018). However, 111 In-NOTA-MNT N-affibody and 111 In-NOTA-MNT C-EGF demonstrates higher cytotoxicity than 111 In-NOTA-MNT N-EGF ( Figure 8).…”
Section: Discussionsupporting
confidence: 91%
“…We investigated the effects of MNT on cell proliferation on the non-atypical cell model MCF-7, for which activation of EGFR leads to mitogenic effect. We used A431 cell line for the other experiments, since the results for the previously described MNT C-EGF were obtained on this cell line (Gilyazova et al, 2006;Rosenkranz et al, 2008;Slastnikova et al, 2012a;Koumarianou et al, 2014;Slastnikova et al, 2017b;Rosenkranz et al, 2018), however for A431 activation of EGFR leads to inhibition of the tumor cell proliferation (Kawamoto et al, 1983;Bromberg et al, 1998). We showed that MNT N-affibody did not affect cell growth ( Figure 10), that was consistent with the properties of this affibody (Friedman et al, 2008;Beuttler et al, 2009;Ekerljung et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another aspect of membrane trafficking constitutes the design of targeting strategies such that some very specific molecules viz. folate receptors (Slastnikova et al, 2017), epidermal growth factor receptros (Rosenkranz et al, 2018), melanocortin receptor-1 (Durymanov et al, 2012), and a-melanocyte stimulating hormone (Rosenkranz et al, 2003), overexpressed on the diseased (e.g. cancerous) cells, act as the target and receptor-specific ligand bearing transportation carriers that are designed for the delivery of therapeutic payloads.…”
Section: Introductionmentioning
confidence: 99%